Application of hydrolyzed proteins of animal origin in processed meat. Issue 2 (6th October 2015) - Meinert, Lene; Broge, Eva Honnens de Lichtenberg; Bejerholm, Camilla; Jensen, Kirsten
Abstract: With increasing consumer interest in functional foods, proteins from slaughterhouse side streams can offer interesting application opportunities in this respect. Worldwide, increasing numbers of people are suffering from hypertension and protein deficiency. Hydrolyzed proteins of animal origin may show ACE‐inhibitory activity, which is central to the treatment of hypertension. Furthermore, the protein content of, for example, meat products increases markedly through the addition of hydrolyzed proteins, and these protein‐rich products are of interest to those suffering from protein deficiency. Through a series of analyses, six selected hydrolysates were analyzed for their application potential in the Danish meat product saveloy. Hydrolyzed pig rectum and bovine diaphragm showed the highest ACE‐inhibitory activities, and these activities were maintained in the processed saveloys. The ACE‐inhibitory activities could not readily be explained by the amino acid profile. The content of N‐compounds in the saveloys increased with increasing addition of hydrolysate, with little difference between the added hydrolysates. A sensory panel assessed the saveloys with added porcine rectum (8%), bovine diaphragm (8%), and bovine heart (4% and 8%) as having the strongest off‐flavors (chemical flavor). No increase in salty taste resulting from the addition of hydrolysates was detected in the saveloys. Finally, the consumers found the saveloys too mild in flavor and recommended the addition of more spices. Abstract : Increasing numbers of people are suffering from hypertension. Hydrolyzed proteins of animal origin show ACE‐inhibitory activity.